Effect of Chrysin on Endoplasmic Reticulum Stress in a Rat Model of Testicular Torsion. Issue 5 (4th May 2022) - Kazaz, Ilke Onur; Demir, Selim; Kerimoglu, Gokcen; Colak, Fatih; Alemdar, Nihal Turkmen; Akman, Ahmet Ugur; Cekuc, Ozan Can; Mentese, Ahmet
Abstract: Background: The purpose of this study was to evaluate the possible therapeutic effect of chrysin (CHS) on testicular torsion/detorsion (T/D) injury in vivo through the mechanisms of oxidative stress and endoplasmic reticulum stress (ERS). Methods: Eighteen male rats were divided into three groups of six subjects in each group: control, T/D and T/D + CHS (100 mg/kg). To evaluate the degree of oxidative stress, tissue malondialdehyde (MDA), total oxidant status (TOS) and total antioxidant status (TAS) levels were determined using colorimetric methods, while tissue superoxide dismutase (SOD) levels were determined using an ELISA kit. To evaluate the degree of ERS, tissue glucose regulatory protein 78 (GRP78), activating transcription factor 6 (ATF6) and C/EBP homologous protein (CHOP) levels were determined using ELISA kits. Johnsen's testicle scoring system was used for histological evaluation. Results: In the T/D group, it is determined that statistically significant decreasing in the levels of TAS, SOD and Johnsen score, and increasing in TOS, MDA, GRP78, ATF6 and CHOP levels compared to control group (p < 0.05). CHS administration statistically significantly restored this T/D-induced damage (p < 0.05). Conclusion: This is the first study to show that CHS prevent T/D-induced testicular damage through its ERS inhibitor activity. More comprehensive studies are needed to understand the underlying mechanisms. Supplemental data for this article is available online at https://doi.org/10.1080/08941939.2021.2015489 .